2007
DOI: 10.1590/s1415-790x2007000100009
|View full text |Cite
|
Sign up to set email alerts
|

Automedicação em idosos na cidade de Salgueiro-PE

Abstract: OBJETIVOS: identificar os determinantes associados ao perfil da automedicação na população de idosos de 60 anos e mais, no município de Salgueiro/Pernambuco/Brasil. MÉTODO: Estudo de corte transversal realizado na zona urbana no município de Salgueiro - PE. Entre 01/05 a 10/06/2004, foram aplicados questionários em uma amostra de 355 indivíduos da população de 60 anos e mais. Os dados foram processados e analisados no EPIINFO 6.04 após digitação em dupla entrada e validação. RESULTADOS: 44,9% dos entrevistados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
40

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 19 publications
2
12
1
40
Order By: Relevance
“…The frequencies were also below those found in a study of residents in Santa Maria, RS, Brazil (53.3%) (15) and in another that evaluated selfmedication in elderly people in Salgueiro, PE, Brazil (77%) (9) . However, the prevalence found in this study was higher than that observed in adult populations of other countries, such as Spain (12.7%) (6) .…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…The frequencies were also below those found in a study of residents in Santa Maria, RS, Brazil (53.3%) (15) and in another that evaluated selfmedication in elderly people in Salgueiro, PE, Brazil (77%) (9) . However, the prevalence found in this study was higher than that observed in adult populations of other countries, such as Spain (12.7%) (6) .…”
Section: Discussioncontrasting
confidence: 69%
“…However, the prevalence found in this study was higher than that observed in adult populations of other countries, such as Spain (12.7%) (6) . The most consumed medications were those for the nervous system (46.7%), while the most used subgroup was analgesics (43.4%), a pattern described by several authors (3,5,9,15) . The results presented here were different from those of another study (11) that identified medications for the cardiovascular system as the most used therapeutic category.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations